Preventive diplomacy in accordance with the United Nations Charter (What it is and the difficulties it faces) - علي, نور; لؤي محمد صيّوح; رامي كاسر لايقه (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of this study was to explore the concept of preventive diplomacy within the framework of the United Nations Charter, present its main applications, discuss the challenges it faces, and identify the reasons for its failure in many cases. To achieve this, the researcher collected information related to preventive diplomacy as a peaceful means to resolve both internal and international conflicts. The study also analyzed the reasons and difficulties encountered by the United Nations in implementing this approach in order to assess its effectiveness in achieving international peace and security. The study reached several conclusions; including the fact, that effective implementation of preventive diplomacy requires a precise understanding of the facts and reasons leading to tensions and conflicts. Additionally, there are various challenges that hinder the effective application of preventive diplomacy. Despite some improvements in crisis management and tension reduction, further efforts are needed to achieve the goal of preventive diplomacy on a larger scale and with greater effectiveness.